1988
DOI: 10.1007/bf00341947
|View full text |Cite
|
Sign up to set email alerts
|

Complications in cerebral angiography with iohexol (Omnipaque) and meglumine metrizoate (Isopaque cerebral)

Abstract: The complications of cerebral angiography have been recorded in 1509 examinations with metrizoate (Isopaque Cerebral) and in 1000 examinations with iohexol (Omnipaque). The frequency of complications was 2.0 percent for metrizoate and 1.3 percent for iohexol. Permanent sequelae were seen in 4 patients, 3 in the metrizoate and one in the iohexol group. One of these patients died, probably from thromboembolism. Blood coagulation parameters were studied during the angiography in 22 patients and only minor, probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Unfortunately, this question was not addressed in a subsequent paper. 30 The authors incidentally found no significant difference in side effects between the different contrast media.…”
Section: Prospective Studiesmentioning
confidence: 96%
“…Unfortunately, this question was not addressed in a subsequent paper. 30 The authors incidentally found no significant difference in side effects between the different contrast media.…”
Section: Prospective Studiesmentioning
confidence: 96%
“…Despite advances, cerebral angiography continues to be used for the examination of patients with cerebrovascular diseases. In the past decade, safer contrast agents have been used and there have been important technical advances including smaller catheters, hydrophylic guide wires, and digital imaging systems (5)(6)(7). The purpose of this prospective study was to identify the risk factors for neurologic complications that are related to cerebral angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Four‐vessel angiographic examination, performed by an experienced neuroradiologist, is usually a straightforward procedure in these patients, but may occasionally be time consuming. Despite improvements of catheters and contrast media, complications to IA‐DSA occur in approximately 1% of the procedures (5, 9). Minimal‐ or non‐invasive methods replacing IA‐DSA could reduce the time before the aneurysm is treated without exposing these patients to the risk of complications to IA‐DSA.…”
mentioning
confidence: 99%